Twin Gestation - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
The copper-T intrauterine contraceptive device is an effective long-acting reversible contraceptive option. However, there exists a slim chance of failure. The Copper T 380A has a 1 year failure rate of 0.8% and a 12 year cumulative failure rate of 2.2%. On long-term basis, the cumulative life failure rate for Copper T 380A is 22/1000 long-acting contraceptives after a single application from the 1stto 10thyear of insertion, comparable to 18.5 for all tubal sterilisation procedures. When failure happens, the patient is usually at the crossroads of either to terminate the pregnancy or continue with the unplanned pregnancy. Therefore, the patient ought to be adequately counselled on management options, which includes termination of pregnancy where there are no restrictive laws, intrauterine contraceptive device (IUCD) removal if accessible otherwise leavein situwith risks of miscarriage, pre-labour rupture of membrane, and pre-term delivery. The patient’s choice is usually laden with emotional and psychological adjustments, especially if the IUCD failed with twin gestation, as seen in this case of a 39-year-old multipara who had Copper-T IUCD inserted 6 months after her last delivery. She opted to carry on with the pregnancy despite associated medical conditions. Attempt at IUCD removal failed at 19 weeks gestational age (GA), and she subsequently drained liquor and was delivered of live pre-term babies at 32 weeks GA. The IUCD was picked up extra chorion and not embedded close to the cervical internal os. Her gestational diabetes and hypertension were co-managed with physicians, while the neonatologists managed the pre-term babies before they were all discharged.